1998
DOI: 10.1046/j.1365-2559.1998.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidal epithelial thymoma (ITET)/carcinoma showing thymus‐like differentiation (CASTLE) exhibits CD5 immunoreactivity: new evidence for thymic differentiation

Abstract: CD5 immunoreactivity in ITET/CASTLE is new evidence in support of thymic differentiation in this neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 13 publications
5
57
1
Order By: Relevance
“…CASTLE is a rare neoplasm which exhibits slow growth and a favourable prognosis [28]. These tumors are immunoreactive with CD5 [29]. In the present study, none of the three cases were immunoreactive with CD5 in contrast to CASTLE.…”
Section: Discussioncontrasting
confidence: 46%
“…CASTLE is a rare neoplasm which exhibits slow growth and a favourable prognosis [28]. These tumors are immunoreactive with CD5 [29]. In the present study, none of the three cases were immunoreactive with CD5 in contrast to CASTLE.…”
Section: Discussioncontrasting
confidence: 46%
“…The majority of thymomas or other malignancies are CD5 negative. 4,10,16 It is reported that expression of high molecular weight keratin (HMWCK), carcinoembryonic antigen (CEA), and p63 in CASTLE are evidence of thymic origin and are useful diagnostic markers to distinguish thyroid CASTLE from other thyroid neoplasms. 13 Ito et al reported a sensitivity and a specificity of 82% and 100%, respectively, for CD5 positive for the diagnosis of CASTLE.…”
mentioning
confidence: 99%
“…Friedman et al reported on fine-needle aspiration of a thymoma mimicking lymphoblastic lymphoma [11]. It has been reported a few times that fine-needle aspi- ration of an ectopic cervical thymoma mimicked a thyroid lymphoid tumor, such as Hashimoto's thyroiditis or malignant lymphoma [12][13][14]. An ectopic thymoma shows the same histological features as mediastinal thymoma.…”
Section: Discussionmentioning
confidence: 99%